Effects of particle sizes, resin content and board density on properties of Sesendok particleboard / Jamaludin Kasim … [et al.] - Kasim, Jamaludin; Mat Yusof, Aisa Amira; Mohd Hashim, Nor Haslinda; Salamat, Noor Adilah (Universiti Teknologi MARA Cawangan Pahang, 2008)
Results of the study show that board density, resin content and particle size significantly affect all the board properties. Large particles significantly increase the properties of MOR and MOE while smaller particle sizes give better IB value. With higher board density, all the strength and dimensional properties are significantly improved. However, Sesendok particleboard does not surpass the standard requirement as defined EN 312/3, especially for thickness swelling.